Regional language effects on accent perception and language attitude: The case of mandarin vs. cantonese speakers in mainland China - Yizhou Lan; Jeroen van de Weijer; Albert Lee (PLoS ONE, 2026)
The perception of L2 English accents has been extensively studied across disparate language groups, yet it remains unclear how these judgments operate among speakers of closely related varieties, where shared linguistic heritage might heighten sensitivity to phonetic differences. This study investigates how L2 English accent judgments operate among L2 English speakers whose L1s belong to the same broader language family. We recruited 164 English learners in mainland China with Cantonese and Mandarin backgrounds defined here by their first-acquired and dominant spoken Chinese variety (i.e., L1/dominant Cantonese vs. L1/dominant Mandarin), and asked them to rate the comprehensibility and accentedness of 12 pre-categorized Mandarin- and Cantonese-accented English short passages of different accent strengths and to rate 18 attitudinal traits concerning the superiority, attractiveness and dynamism of those same short passages. Two native English short passages were also added as controls. Results show that the native English speakers were rated less accented than and socially superior to both Mandarin- and Cantonese-accented English regardless of accent strengths. Both Cantonese and Mandarin speakers tended to rate Cantonese-accented English as more accented than Mandarin-accented ones, although both had similar level of comprehensibility. In terms of language attitude, Cantonese-accented English was rated as more friendly but lower-class compared to Mandarin-accented English in some aspects, whereas Mandarin-accented English was rated as more dynamic than and superior to Cantonese-accented English by both L1 Cantonese and Mandarin speakers. Results show that both Cantonese and Mandarin speakers of English considered native English as the superior variant of accent.